LEGAL TRANSLATION – A MULTIDIMENSIONAL ENDEAVOUR - SCOTT, Juliette (Comparative Legilinguistics, 2022)
Legal translation is a highly skilled task. It has even been described as the “ultimate linguistic challenge” (Harvey 2002: 177). However, law firms or corporations that procure translations from self- employed translation practitioners often find the intricacies of the task difficult to perceive. Following extensive fieldwork examining how legal translation is commissioned and performed in ‘outstitutional’ contexts, I have developed a multidimensional model which illustrates the legal translator’s textual agency, aimed at conveying the complexities of translation performance to clients and other stakeholders. It may also serve to train fledgling legal translators, and to heighten practising translators’ awareness of their overall task. The impetus for the model sprang primarily from findings of serious information asymmetry and goal divergence in the market, and evidence that actors involved do not grasp (a) the need for legal translators to be fully briefed, or (b) the layers of skills involved.